Ex Vivo Comparison of Bursting Strength of Ventral Median and Right Ventral Paramedian Celiotomies in Horses1. Issue 4 (21st February 2013) - Anderson, Stacy L.; Bracamonte, José L.; Hendrick, Steve; Carmalt, James L.; Wilson, David G.
Abstract Objective To compare bursting strength and failure mode between ventral median (VM) and right ventral paramedian (RVP) celiotomies closed with 1 section of USP 7 braided polydioxanone (7PD). Study Design Ex vivo experimental. Animals Equine cadavers (n = 12). Methods A 25 cm VM or RVP (positioned 5 cm lateral to the linea alba) celiotomy was created in fresh equine cadavers. A 200 L polyurethane bladder was inserted into the abdomen. Celiotomies were closed in a simple continuous pattern with 1 section of 7PD. The bladder was inflated with compressed air until construct failure. Horse signalment, body weight, celiotomy type, failure mode (suture or abdominal wall), failure location (adjacent or remote from the celiotomy), and bursting strength (mmHg) were recorded. Interactions between independent and dependent variables were assessed with statistical tests including linear regression. Results Increasing age (P = .002) and Quarter horse‐type breed (P = .01) had a negative effect on bursting strength. When age and breed were controlled, RVP celiotomies had a lower bursting strength compared with VM celiotomies (P = .039). None of the celiotomies failed at the suture. Conclusion VM celiotomies have a greater bursting strength than RVP celiotomies when age and breed are controlled. Celiotomy bursting strength decreases with increasing age and is lower in Quarter horse‐type breeds compared with non‐Quarter horse‐type breeds.